NAHDLATUL ULAMA’S DA’WAH STRATEGIES AGAINST ONLINE GAMBLING AMONG ADOLESCENTS IN PAYA BAKUNG VILLAGE - Al Fatih, Siti Karmela; Rubino (Pena Cendekia Insani, 2025)
This study analyses the strategies of Nahdlatul Ulama (NU) in addressing the growing issue of online gambling among adolescents in Paya Bakung Village, Deli Serdang Regency. Using a qualitative approach through observation, documentation, and in-depth interviews, the research identifies three main da’wah strategies sentimental, rational, and sensory. The findings show that NU’s approaches have contributed to reducing adolescent involvement in online gambling by strengthening religious awareness and community values. However, their effectiveness remains limited due to economic pressures, easy access to gambling platforms, and the lack of structured follow-up. The study highlights the need for continuous collaboration between NU, families, and educational institutions to reinforce religious and ethical values as well as to provide sustainable preventive measures.